NCOA1 is a novel susceptibility gene for multiple myeloma in the Chinese population: A case-control study. - Mengle Peng; Guanfei Zhao; Funing Yang; Guixue Cheng; Jing Huang; Xiaosong Qin; Yong Liu; Qingtao Wang; Yongzhe Li; Dongchun Qin (PLoS ONE, 2017)
Multiple myeloma (MM) is an incurable malignancy of mature B-lymphoid cells, and its pathogenesis is only partially understood. Previous studies have demonstrated that a number of Non-Hodgkin Lymphoma (NHL) associated genes also show susceptibility to MM, suggesting malignancies originating from B cells may share similar genetic susceptibility. Several recent large-scale genome-wide association studies (GWAS) have identified HLA-I, HLA-II, CXCR5, ETS1, LPP and NCOA1 genes as genetic risk factors associated with NHL, and this study aimed to investigate whether these genes polymorphisms confer susceptibility with MM in the Chinese Han population. In 827 MM cases and 709 healthy controls of Chinese Han, seven single nucleotide polymorphisms (SNPs) in the HLA-I region (rs6457327), the HLA-II region (rs2647012 and rs7755224), the CXCR5 gene (rs4938573), the ETS1 gene (rs4937362), the LPP gene (rs6444305), and the NCOA1 region (rs79480871) were genotyped using the Sequenom platform. Our study indicated that genotype and allele frequencies of rs79480871 showed strong associations with MM patients (pa = 3.5×10-4 and pa = 1.5×10-4), and the rs6457327 genotype was more readily associated with MM patients than with controls (pa = 4.9×10-3). This study was the first to reveal the correlation between NCOA1 gene polymorphisms and MM patients, indicating that NCOA1 might be a novel susceptibility gene for MM patients in the Chinese Han population.